Algunhas consideracións sobre a posición do adxectivo nunha fala galega - Alonso Núñez, Aquilino Santiago (Madrygal. Revista de Estudios Gallegos, 2011)
This study, from Galician speech, has some general information on the placement of noun phrases in the subclasses of adjectives. We conclude that the preemption of the adjective in Galician is a resource that the speaker has, in order to make a value judgment or to highlight an expressive adjective.
Keywords: Galician; adjective; adjective syntax; word order.